Muhammadiyah's Criticism Towards Government Policies in The Era of Din Syamsudin’s Leadership - Tohari Tohari; Sjafri Sairin; Muhammad Azhar; Muhammad Nurul Yamin (Al-Albab, 2020)
The liberalization policy through Law No. 7 of 2004 concerning Natural Resources and Law No. 22 of 2001 concerning Oil and Gas, elicited a strong reaction from the Muhammadiyah movement. In response to the laws, Muhammadiyah used their role as both a civil society movement and Islamic movement and took the step of constitutional jihad. This article looks at the steps and attitudes of Muhammadiyah's criticism towards government policies under the administration of President Susilo Bambang Yudoyono (SBY). The findings showed the constitutional jihad was based on the spirit of the Muhammadiyah indictment and the spirit of progressive Islam Muhammdiyah. It was within this spirit that the Muhammadiyah movement was encouraged to be critical of SBY's policies. This study also explores Muhammadiyah's critical attitude which has had an internal and external impacts on the movement as a whole and Muhammadiyah leaders. Muhammadiyah's critical attitude is a form of action and rational choice. The rational choice being made by Muhammadiyah through observation of the impacts of the application of the two laws. Muhammadiyah and its leaders indicate the rational choice of Muhammadiyah actors based on Muhammadiyah's spirit orientation, and the social conditions of the Indonesians in response to the application of both of these laws.